PENINGKATAN KEMAMPUAN KONEKSI MATEMATIS SISWA SMP MELALUI PEMBELAJARAN INKUIRI MODEL ALBERTA - Badjeber, Rafiq; Fatimah, Siti (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2015)
This research was conducted based on the fact that there was a lack in studentâs mathematical connection ability. The aim of this research was to examine the enhancement of studentâs mathematical connection ability by Alberta model inquiry learning. This research used nonequivalent control group design. Population of this research was all eighth-grade students at one of the junior high schools in Palu, and the samples were two classes selected by using purposive sampling technique, in which they were used as an experimental class and control class. The experimental class was treated by Alberta Model inquiry learning and control class by conventional learning. Instruments used in this research were mathematics connection ability test and observation sheet. Results showed that studentâs mathematical connection ability enhancement in students received Alberta model inquiry learning was better than students who received conventional learning.Keywords: Inquiry Learning of Alberta Model, Mathematical Connection AbilityABSTRAKPenelitian ini didasarkan pada kenyataan bahwa terdapat permasalahan masih rendahnya kemampuan koneksi matematis siswa. Tujuan penelitian ini adalah untuk mengkaji peningkatan kemampuan koneksi matematis siswa yang memperoleh pembelajaran inkuiri model Alberta. Penelitian menggunakan nonequivalent control group design. Populasi dalam penelitian ini adalah seluruh siswa kelas VIII salah satu SMP di Kota Palu dan sebagai sampel dipilih siswa dari dua kelas dengan menggunakan teknik purposive sampling untuk dijadikan sebagai kelas eksperimen dan kelas kontrol. Kelas eksperimenÂ  diberi pembelajaran inkuiri model Alberta dan kelas kontrol pembelajaran konvensional. Instrumen dalam penelitian ini adalah tes kemampuan koneksi matematis dan lembar observasi. Hasil penelitian menunjukkan bahwa peningkatan kemampuan koneksi matematis siswa yang memperoleh pembelajaran inkuiri model Alberta lebih baik daripada siswa yang memperoleh pembelajaran konvensional.Kata kunci: Pembelajaran Inkuiri Model Alberta, Kemampuan Koneksi Matematis